Morphological and Molecular Identification of Cimex hemipterus Fabricius, 1803 (Hemiptera: Cimicidae) and First Report of C. lectularius Linnaeus, 1758, in Madagascar. Issue 3 (11th March 2022) - Akhoundi, Mohammad; Raharisoa, Annie; Andrianjafy, Romain Lovanirina; Chebbah, Dahlia; Razanakolona, Lala Rasoamialy-Soa; Izri, Arezki
Abstract: Bed bugs are hematophagous insects with a long history of presence in human communities. Over the last three decades, infestations by bed bugs in human dwellings have drastically increased, leading to a rise in bed bug concerns. This study was conducted in May 2019 in the Miarinarivo district of Madagascar. Eight locations with suspected infestations were inspected. Of these, five locations were found with active bed bug infestations. Overall, 23 (19 adults and four nymphs) specimens with numbers per apartment ranging from 2 to 6 were collected and analyzed using morphological and molecular approaches. Of 19 adults collected, 18 were morphologically identified as Cimex hemipterus (Hemiptera: Cimicidae), with the final adult identified as C. lectularius . Morphological identification of adults was confirmed by sequencing 450 bp fragment of COI gene. All four nymphs were also identified molecularly as C. hemipterus . Maximum likelihood phylogenetic tree of COI gene and sequence alignment of C. hemipterus specimens revealed the presence of two groups (first group clustered with previously reported haplotype from Asian and African countries and the second group encompassed a lesser known haplotype exclusively from Africa (Kenya and Senegal). This study presents low genetic diversity among C. hemipterus specimens and, for the first time, reports the occurrence of C. lectularius, known as temperate species, in Madagascar. These results can be helpful in control management strategies against these ectoparasites in this country.